Antimicrobial and Antioxidant Activities of Different Extracts of Helichrysum arenarium subsp. (L.) Moench aucheri - Eren, Ayşe; İnci, Şule; Khasro, Kochar; Kırbag, Sevda; Güven, Kemal (My University, 2023)
Helichrysum arenarium (L.) Moench subsp. aucheri is a herbaceous perennial herb belonging to the Asteraceae. This plant has biological activities such as antibacterial, antiviral, anti-inflammatory, antifungal, antiproliferative, antioxidant, and antiradical. In this study, antimicrobial and antioxidant activities of methanol and ethanol extracts of aerial parts of H. arenarium subsp. aucheri were investigated. To determine the antimicrobial activity pathogenic microorganisms Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, Bacillus megaterium, Candida glabrata, Candida albicans and Trichophyton sp. Antioxidant activity was determined with total antioxidant value (TAS), total oxidant value (TOS) and 2.2-diphenyl-1-picrylhydrazil (DPPH) radical scavenging capacity. In the results obtained, it was determined that the methanol extract had an antimicrobial effect (9.3 mm) only against C. albicans. It was found that the ethanol extract showed antimicrobial activity at different rates (8.8-20.4 mm) against S. aureus, B. megaterium, C. glabrata, C. albicans and Trichophyton sp. The TAS value of the methanol extract was 3.00 mmol, and the TAS value of the ethanol extract was 3.15 mmol. The TOS value of the methanol extract of the same species was calculated as 6.81 ?mol, and the TOS value of the ethanol extract was calculated as 12.64 ?mol. The DPPH radical scavenging effects of extracts of goldengrass was found to increase depend on concentrations.
Keywords: Helichrysum arenarium; Antimicrobial effect; antioxidant effect; goldengrass